2022
DOI: 10.3390/molecules27051663
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Behavior of Antimony Oxyanions in Water: Influence of pH, Inorganic and Organic Matter on the Physicochemical Characteristics of Iron Precipitates

Abstract: The presence of inorganic and organic substances may alter the physicochemical properties of iron (Fe) salt precipitates, thereby stabilizing the antimony (Sb) oxyanions in potable water during the chemical treatment process. Therefore, the present study aimed to examine the surface characteristics, size of Fe flocs and coagulation performance of Sb oxyanions under different aqueous matrices. The results showed that surface properties of Fe flocs significantly varies with pH in both Sb(III, V) suspensions, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(79 reference statements)
1
6
0
Order By: Relevance
“…It is speculated that the oxidation and reducibility of Fe affect the adsorption and precipitation of Sb, which is consistent with the experimental results of [43] that after curing for more than 5 days, the stability effect of ferrite, FeSO 4 on Sb all decreased slightly. The results of [44] have showed that the presence of inorganic and organic matter changed the physicochemical properties of the iron salt precipitation, in turn affected the adsorption and precipitation of Sb during the stabilization process.…”
Section: Influence Of Feso 4 On As and Sb Leaching Concentrationsmentioning
confidence: 99%
“…It is speculated that the oxidation and reducibility of Fe affect the adsorption and precipitation of Sb, which is consistent with the experimental results of [43] that after curing for more than 5 days, the stability effect of ferrite, FeSO 4 on Sb all decreased slightly. The results of [44] have showed that the presence of inorganic and organic matter changed the physicochemical properties of the iron salt precipitation, in turn affected the adsorption and precipitation of Sb during the stabilization process.…”
Section: Influence Of Feso 4 On As and Sb Leaching Concentrationsmentioning
confidence: 99%
“…The 1000 mg/L (417 mgC/L) stock solution of humic acid (HA) was prepared by adding HA powder in pure water. The sodium hydroxide (NaOH) solution was used to adjust pH of HA stock solution to 11 and was stirred at 100 rpm for 24 h [29]. This model organic matter is widely used to simulate natural water conditions [18,24].…”
Section: Preparation Of Stock Solutions and Test Samplesmentioning
confidence: 99%
“…The predetermined quantity of FC dosage was first supplied to test samples in all trials during a rapid coagulation phase followed by a pH adjustment to 7, which is close to real groundwater conditions. The experimental procedure was then executed using a jar tester apparatus (Model: SJ-10, Young Hana Tech Co., Ltd., Gyeongsangbuk-Do, Korea) in various phases: Flash mixing phase (coagulation at 140 rpm for 3 min); slow mixing phase (flocculation at 40 rpm for 20 min); and sedimentation phase (settling of particles for 30 min) [24,25,29,31]. The aliquots were collected after experimental procedure and analyzed for quantifying TOC content using an unfiltered sample using a TOC analyzer (TOC-5000A, Shimadzu Corp, Kyoto, Japan).…”
Section: Experimental Procedures and Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The stabilization mechanism may be the direct reaction between iron ions and Sb to form a precipitate, as well as the adsorption of Sb by its hydrolysate. The results of Inam et al (2022) showed that the presence of inorganic and organic matter changes the physicochemical properties of iron salt precipitate, thereby affecting the adsorption and precipitation of antimony anions during the stabilization process.…”
Section: Sulfate Affect the Mobility Of Arsenic Andmentioning
confidence: 99%